Renal hemodynamics disturbances and microalbuminuria in young patients with arterial hypertension - I. G. Fomina; E. N. Gavrilova; N. E. Gaidamakina; T. A. Dyakova; D. A. Zateyshchikova (Кардиоваскулярная терапия и профилактика)
Aim. To identify the first clinical signs of renal pathology in young patients (under 35) with initial stages of arterial hypertension (AH). Material and methods. Fifty-seven men with Stage I-II AH, aged 15-35, were examined. Exclusion criteria were: secondary AH, chronic renal or urologic pathology, diabetes mellitus in anamnesis. In all participants, renal dynamic angioscintigraphy with DTPA-Tc99m, and ophtalmoscopy, to determine the stage of hypertensive rethinopathy, were performed. In 27 patients, 24-hour microalbuminuria (MAU) was assessed. Results. Renal dynamic angioscintigraphy with DTPA-Tc99m revealed various renal hemodynamics abnormalities in 98% of the patients (n=56). In most individuals (94%; n=53), renal blood flow was reduced bilaterally. Significant bilateral reduction of renal blood flow, of Stage II-III (<420 ml/min, with norm of 690±60 ml/min), was registered in 39 individuals (68%). MAU was revealed in 8 out of 27 examined patients (30%); its mean level was 64.8±15.2 mg/l. Participants with MAU more often experienced Stage II-III decrease in renal blood flow (<420 ml/min, with norm of 690±60 ml/min). Conclusion. At early AH stages, young male patients, aged under 35, experienced renal function remodeling, despite short AH duration. The remodeling manifested in renal blood flow decrease, glomerular filtration rate disturbances, and MAU development.